2021
DOI: 10.1186/s43044-021-00140-1
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian practical guidance in lipid management 2020

Abstract: Background Numerous epidemiological investigations and randomized clinical studies have determined that dyslipidemia is a major contributor to atherosclerotic cardiovascular disease (ASCVD). Consequently, the management of serum cholesterol and low-density lipoprotein levels has become a central objective in the effort to prevent cardiovascular events. Main body Many guidelines were issued by different organizations and societies to define patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…The postprandial rise in TG is usually small, between 12 and 27 mg/dL. Fasting lipid testing is preferred in patients with metabolic syndrome, family history of premature ASCVD or genetic lipid disorders, non-fasting TG ≥ 400 mg/dL and to assess adherence to lifestyle interventions and lipid lowering medications [ 7 , 9 , 18 , 23 , 24 ].…”
Section: Scope Of the Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The postprandial rise in TG is usually small, between 12 and 27 mg/dL. Fasting lipid testing is preferred in patients with metabolic syndrome, family history of premature ASCVD or genetic lipid disorders, non-fasting TG ≥ 400 mg/dL and to assess adherence to lifestyle interventions and lipid lowering medications [ 7 , 9 , 18 , 23 , 24 ].…”
Section: Scope Of the Articlementioning
confidence: 99%
“…We have previously published a consensus statement on the management of lipids [ 18 ]. We felt that there was a need to address an ignored and frequently overlooked part in the management of dyslipidemia which was hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, 46% of overall deaths are related to cardiovascular diseases (CVD) [ 17 , 18 ]. Dyslipidemia increases the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia increases the risk of CVD. Several studies showed that high blood cholesterol had been found in 37% of Egyptians [ 18 20 ]. Hydroxymethyl glutaryl-CoA (HMG-CoA) reductase inhibitors (statins) are the primary pharmacotherapy for dyslipidemia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 37% percent of population in Egypt is subjected to have higher blood cholesterol levels as per the observation from various researchers. Many risk factors can be expected to evolve, which are responsible for the development of atherosclerotic cardiovascular diseases; therefore, it becomes essential factor to assess the nature of cardiovascular risk before it becomes imperative 28 . As per the definition stated in the background, Hyperlipidemia is a medical condition which is characterized by the observation of increase any or all lipids profile and lipoproteins in the blood.…”
Section: Introductionmentioning
confidence: 99%